The Steel Evolutionary Spine Revisited, with Implications and Consequences - Richard H. Zander (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
Fractal evolution is apparently effective in selectively preserving environmentally resilient traits for more than 80 million years in Streptotrichaceae (Bryophyta). The modern bryoflora first appeared in mid to late Cretaceous times, about 80–100 mya. Analysis simulated the maximum destruction of ancestral traits in that large lineage. Constraints enforced were the preservation of the newest ancestral traits, and all immediate descendant species obtained different new traits. Assuming the generation of one genus from an ancestral species in another genus takes 22 ± 17.25 mya on average, and assuming a punctuated equilibrium burst of descendant generation, then the number of ancestor-to-ancestor steps measures the temporal depth of a lineage. Maximum character state changes of ancestral traits were 16 percent of all possible traits in any one sub-lineage, or 73 percent total of the entire lineage. Results showed, however, that only four ancestral traits are permanently eliminated in any one lineage or sub-lineage. A lineage maintains maximum biodiversity of temporally and regionally survival-effective traits at minimum expense to resilience across geologic time of 88 million years for the group studied. Similar processes generating extant punctuated equilibrium as bursts of about four descendants per genus and one genus per 1–2 epochs are possible in other living groups given similar emergent processes. The mechanism is considered complexity-related, the lineage is a self-organized emergent phenomenon strongly maintained in the ecosphere by natural selection on fractal genera. For this re-evaluation, an addendum discusses the prospect of human long-term survival, the isomorphism of human and moss lineage preservation, and finally the problems for systematic biology and all of evolutionary study generated by a conflict between analysis by shared ancestry and ancestor-descendant trait changes.